Astaxanthin-loaded emulsion gels stabilized by Maillard reaction products of whey protein and flaxseed gum: Physicochemical characterization and in vitro digestibility. (June 2021) - Zhang, Zhao; Chen, Wenchao; Zhou, Xin; Deng, Qianchun; Dong, Xuyan; Yang, Chen; Huang, Fenghong
Graphical abstract: Highlights: Ultrasound significantly influenced the Maillard reaction of whey protein and flaxseed gum. The quality and stability of emulsion gels stabilized by Maillard reaction products were enhanced by ultrasonic treatment. Emulsion gels significantly retarded the in vitro digestion and improved the bioaccessibility of astaxanthin. Abstract: In order to evaluate the effect of ultrasound and Maillard reaction on the physicochemical properties and gastrointestinal fate of astaxanthin-loaded emulsion gels, the Maillard reaction products (MRPs) of whey protein and flaxseed gum (FG) were prepared by traditional or ultrasonic assisted wet-heating. The MRPs obtained by ultrasonic assisted wet-heating had higher grafting degree and more expanded structures evidenced by the browning intensity, fluorescence intensity and circular dichroism (CD) analysis, thus enhancing its functional properties like solubility and emulsifying capacity. The MRPs improved the water holding capacity, encapsulation efficiency, stability of emulsion gels, in which astaxanthin was wrapped as a model bioactive compound. During the simulated digestion process, the bioaccessibility of loaded astaxanthin reached 72.08% for the emulsion gels stabilized by MRPs. The results highlighted the potential of MRPs in improving functionality of protein and as a delivery carrier of bioactive compounds in food industry.